Effects of Training and Development, Organizational Culture, Job Satisfaction, and Career Development on Employee Retention in Commercial Banks in Bangladesh - Md. Atikur Rahaman; Md. Sayed Uddin; Wasib Latif (Korea Institute of Science and Technology Information, 2023)
In the current era of globalization, financial and banking organizations have been facing ever-growing challenges in the global market regarding retention, customer satisfaction, commitment, engagement, proper services, and the belief of their employees. Employees are regarded as an enormous asset for every organization that plays an important role in achieving the vision of the company. The objective of this study is to explore the determinants of bank employee retention and its impact on an organization in the context of Bangladesh. In terms of research purpose, non-probability convenience sampling has been used in this study, and the targeted population was the commercial bank employees of Bangladesh. In terms of data collection, the researchers have used the adopted questionnaires from previous studies. In this study, the total sample size was 180, and a questionnaire was sent to the respondents through e-mails. For analyzing the collected data, SPSS 26.0 version has been used to test the study model and the proposed hypotheses. This study shows that there were four independent variables training and development, organizational culture, job satisfaction, and career development have a positive and significant impact on employee retention. So, the bank management should organize the retention program for the welfare of the employees.